Caregiving Within Fragile Boundaries: Subjective Burden Experiences of Caregivers of Children with Hemophilia and Comorbidities (Jurnal Psikologi Udayana, 2026)
This study’s goal is to explore the experience of a caregiver's subjective burden in raising a child who suffers from hemophilia with medical comorbidities. Furthermore, the study employed a qualitative approach with an Interpretative Phenomenological Analysis (IPA) as the research method. The chosen participant is a 40-year-old biological mother (primary caregiver) who has been caring for a child with hemophilia type A and epilepsy comorbidity for 11 years. Data were collected through four semi-structured in-depth interviews. Thematic analysis identified three main themes: (1) Caregiver’s psychological experiences in caring for children; (2) Adaptation processes and self-change; and (3) The meaning of the role of caregiving and orientation towards the child's future. The findings indicate that comorbidities increase the complexity of care and exacerbate the caregiver's subjective burden through demands for ongoing vigilance and limited emotional support. Conceptually, this study confirms that subjective burden is formed by the interaction of medical, psychological, and relational factors. Practical implications emphasize the importance of psychoeducation and psychological interventions for caregivers of chronic illnesses in Indonesia.
Keywords: Subjective Burden; Caregiver; Phenomenology; Hemophilia; Comorbidity